A transcriptional network required for bradyzoite development in Toxoplasma gondii is dispensable for recrudescent disease - Sarah L. Sokol-Borrelli; Sarah M. Reilly; Michael J. Holmes; Stephanie B. Orchanian; Mackenzie D. Massmann; Katherine G. Sharp; Leah F. Cabo; Hisham S. Alrubaye; Bruno Martorelli Di Genova; Melissa B. Lodoen; William J. Sullivan; Jon P. Boyle (Nature Communications, 2023)
Abstract Identification of regulators of Toxoplasma gondii bradyzoite development and cyst formation is the most direct way to address the importance of parasite development in long-term persistence and reactivation of this parasite. Here we show that a T. gondii gene (named Regulator of Cystogenesis 1; ROCY1) is sufficient for T. gondii bradyzoite formation in vitro and in vivo. ROCY1 encodes an RNA binding protein that has a preference for 3’ regulatory regions of hundreds of T. gondii transcripts, and its RNA-binding domains are required to mediate bradyzoite development. Female mice infected with ΔROCY1 parasites have reduced (>90%) cyst burden. While viable parasites can be cultivated from brain tissue for up to 6 months post-infection, chronic brain-resident ΔROCY1 parasites have reduced oral infectivity compared to wild type. Despite clear defects in bradyzoite formation and oral infectivity, ΔROCY1 parasites were able to reactivate with similar timing and magnitude as wild type parasites for up to 5 months post-infection. Therefore while ROCY1 is a critical regulator of the bradyzoite developmental pathway, it is not required for parasite reactivation, raising new questions about the persisting life stage responsible for causing recrudescent disease.